Host Specificity of Flagellins from Segmented Filamentous Bacteria Affects Their Patterns of Interaction with Mouse Ileal Mucosal Proteins - Chen, Huahai (Appl Environ Microbiol, 2017)
Segmented filamentous bacteria (SFB) are known modulators of the mammalian immune system. Currently, the technology for investigating SFB culture in vitro is immature, and as a result, the mechanisms of SFB colonization and immune regulation are not yet fully elucidated. In this study, we investigated the gene diversity and host specificity of SFB flagellin genes. The fliC1 and fliC2 genes are relatively conserved, while the fliC3 and fliC4 genes are more variable, especially at the central and C-terminal regions. Host specificity analysis demonstrated that the fliC1 genes do not cluster together based on the host organism, whereas the fliC3 and fliC4 genes were host specific at the nucleotide and deduced amino acid levels. SFB flagellin protein expression in the ileum mucosa and cecal contents was detected by using fluorescence in situ hybridization (FISH) combined with immunohistochemical (IHC) analysis, immunoblotting, and liquid chromatography-tandem mass spectrometry (LC-MS/MS). Although the purified SFB FliC3 protein originating from both mouse and rat was able to activate Toll-like receptor 5 (TLR5)-linked NF-κB signaling, no host specificity was observed. Interestingly, the patterns of interaction with mouse ileum mucosal proteins were different for mouse FliC3 (mFliC3) and rat FliC3 (rFliC3). Gene Ontology (GO) and KEGG analyses indicated that more adherence-related proteins interacted with mFliC3, while more lysosome- and proteolysis-related proteins interacted with rFliC3. In vitro degradation experiments indicated that the stability of rFliC3 was lower than that of mFliC3 when they were incubated with mouse ileum mucosal proteins. In summary, the gene diversity and host specificity of SFB flagellin genes were investigated, and SFB flagellin expression was detected in gut samples. IMPORTANCE Since SFB genomes contain only one copy of each FliC gene, the diversity of FliC is representative of SFB strain diversity. Currently, little is known regarding the diversity and specificity of members of the group of SFB. The work presented herein demonstrates that select SFB strains, exhibiting unique FliC patterns, are present in a variety of mammalian hosts. SFB fliC genes were found to interact with a number of unique targets, providing further evidence for SFB host selection. Together, this work represents a major advancement in identifying SFB and delineating how members of the group of SFB interact with the host. Future examination of FliC genes will likely enhance our knowledge of intestinal colonization by the gut microbiota.